INTRODUCING YOUNG PEOPLE TO SAFE USAGE OF TECHNICAL DEVICES - MASTALERZ, Elzbieta (Trends in education, 2014)
This article presents the outline of goals in technical education in regards to preparing elementary and high school students to use popular technical devices. Suggestions from core curriculum are listed, and results of research, conducted among early teenagers, showing technical devices base usage rules knowledge, are described.
Keywords: technical devices; technical education; teenagers.